Implementation of tandem walking and balance exercise combination for fall prevention among older adults with balance disorders : A case study - Lisdahayati Lisdahayati; Gunardi Pome; Saprianto Saprianto; Umar Hasan Martadinata; Nelly Rustiati; Ratna Sukmawati (Lentera Perawat, 2025)
Background: The aging process leads to a progressive decline in physiological function, including muscle strength and body balance, which increases the risk of falls among older adults. Falls are one of the leading causes of injury-related morbidity and mortality in the elderly, significantly reducing quality of life.. Objective: This study aimed to implement a combination of tandem walking and balance exercises as an intervention to prevent falls in older adults with balance impairments at the Tanjung Agung Community Health Center. Methods: A descriptive case study design with a nursing process approach was applied. Two elderly participants with moderate fall risk, as assessed by the Berg Balance Scale (BBS), were included. The intervention consisted of tandem walking and balance exercise sessions twice weekly for four weeks. Balance outcomes were measured pre- and post-intervention using the BBS, complemented by structured interviews and direct observation.. Results: Both participants demonstrated improvement in balance performance. The BBS score of Participant 1 increased from 40 to 51, shifting from moderate to low fall risk. Participant 2 improved from 39 to 46, reflecting enhanced postural stability, though still within moderate risk. Both reported greater confidence and stability during standing and walking, with reduced reliance on external support. Conclusion: The combination of tandem walking and balance exercises was effective in improving static and dynamic balance while reducing fall risk in older adults with balance disorders. This intervention is recommended as a practical fall-prevention strategy in community and primary healthcare settings.